2018
DOI: 10.3390/agronomy8100197
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Characteristics of Different Quinoa (Chenopodium quinoa Willd.) Cultivars Grown under Field Conditions in Southwestern Germany

Abstract: Due to its highly nutritive compounds, the demand for quinoa, a small grain originating from the Andean region of South America, increased rapidly over the last years. However, the main producing countries Bolivia and Peru cannot cover the growing demand. Therefore, the interest of European farmers in cultivating quinoa as a profitable source of income rose very fast. Thanks to a broad genetic diversity an adaption to various climatic conditions is possible. The objective of this study was to evaluate the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
84
6
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 59 publications
28
84
6
3
Order By: Relevance
“…Crude protein content is reported to have a positive and significant correlation with root density (Präger et al, 2018). The currently investigated quinoa has 13.34% crude protein, which is in accordance with the stated percentage between 11 and 15 from Guzman-Maldonado and Paredes-Lopez (1998).…”
Section: Crude Protein Content Moisture and Ashsupporting
confidence: 85%
“…Crude protein content is reported to have a positive and significant correlation with root density (Präger et al, 2018). The currently investigated quinoa has 13.34% crude protein, which is in accordance with the stated percentage between 11 and 15 from Guzman-Maldonado and Paredes-Lopez (1998).…”
Section: Crude Protein Content Moisture and Ashsupporting
confidence: 85%
“…The average seed yield obtained in the first and second year (0.7 and 0.4, respectively) was lower than that reported for the same cultivar under field conditions (2.4 Mg/ha (Cocozza et al, 2013), 2.3 Mg/ha (Razzaghi, Ahmadi, Jacobsen, Jensen, & Andersen, 2012;Razzaghi, Plauborg, et al, 2012), 2.5 Mg/ha (Pulvento et al, 2012) and 1.98 Mg/ha (Präger, Munz, Nkebiwe, Mast, & Graeff-Hönninger, 2018)).…”
Section: Ta B L Econtrasting
confidence: 68%
“…Moreover, under irrigated conditions, seed yield was greater at Bunda (237-3019 kg/ha) than Bembeke (62-692 kg/ha). In support, Präger et al [74] observed significant differences in seed weight between growing seasons and the varieties. Hence, different environmental conditions can contribute to differential results and hence, more trials and field evaluations must be employed repetitively to ascertain the most appropriate variety for specific conditions.…”
Section: Botanical and Agronomic Featuresmentioning
confidence: 76%